APHORISM AS AN OBJECT OF LINGUISTIC RESEARCH IN UZBEK LINGUISTICS - Narmuratov Zayniddin Radjabovich; Safarmurodov Ilkhom Turakulovich (Лучшие интеллектуальные исследования, 2024)
Abstract. This article analysis research on aphorisms in Uzbek linguistics has been studied. Aphorism as a paremiological unit has been analyzed and a response to the research has been given.